Performance of aphid, Aphis craccivora on different host plants - Routray, S; Hariprasad, K V; Manjula, K; Anil Kumar, P; Latha, P (Indian Journal of Plant Protection, 2020)
Performance of Aphis craccivora Koch (Aphididae; Hemiptera) on different host plants viz., cowpea, groundnut, cotton, sunflower, green gram and black gram was studied under laboratory conditions of 28±2°C temperature and 75-80% RH at S.V. Agricultural College, Tirupati, Andhra Pradesh. The total life cycle of A. craccivora was longest (336.0 ± 37.9 hr) on cowpea and shortest on cotton (92.4 ± 9.8 hr). Morphometrical data showed that aphids reared on cowpea were much bigger and gave birth to more number of young ones (52.0 ± 10.9), followed by groundnut (21.1 ± 2.6), green gram (12.6 ± 8.3) and black gram (9.8 ± 8.6). Highest nymphal mortality and zero fecundity of aphids reared on cotton and sunflower have given the status of least preferred host for growth, development and multiplication of aphids. The ranking of different host plants in terms of their preference (from most preferred to least preferred) for growth, development and multiplication of A. craccivora were in the order of cowpea > green gram > black gram > groundnut > sunflower > cotton. Studies on host plant’s physical characters revealed that trichome densities present on leaves of different host plants were negatively correlated with aphid’s performance in terms of adult longevity, fecundity and total life span; and positively correlated with percentage nymphal mortality of A. craccivora. Biochemical analysis of different host plants, showed that protein content of different host plants had a significant negative impact on the total nymphal duration of A. craccivora however they had a positive correlation with the fecundity of A. craccivora. Phenol content of host plants was significantly negatively correlated with aphid’s performance in terms of biological parameters such as total nymphal duration, adult longevity, fecundity and total life span; phenols also had a significant positive correlation with nymphal mortality. Free amino acids had a high degree of positive correlation with aphid’s biological parameters such as adult longevity, fecundity and total life span. Reducing sugars were negatively correlated with nymphal durations, fecundity, adult longevity and total life span of A. craccivora.